Kraft Black Liquor as a Carbonaceous Source for the Generation of Porous Monolithic Materials and Applications toward Hydrogen Adsorption and Ultrastable Supercapacitors - Poupart, Romain (Langmuir : the ACS journal of surfaces and colloids, 2023)
High internal phase emulsions (HIPEs) have templated self-standing porous carbonaceous materials (carboHIPEs) while employing Kraft Black Liquor, a paper milling industry byproduct, as a carbon precursor source. As such, the starting emulsion has been prepared through a laboratory-made homogenizer, while native materials have been characterized at various length scales either with Raman spectrometry, X-ray diffraction (XRD), mercury intrusion porosimetry, and nitrogen absorption. After thermal carbonization, specific surface areas ranging from ∼600 m2 g-1 to 1500 m2 g-1 have been reached while maintaining a monolithic character. Despite a poor graphitization yield, the carbonaceous materials offer good electronic transport properties, reaching 31 S m-1. When tested toward energy storage applications, the native unwashed materials revealed a hydrogen storage of 0.07 wt % at 40 bar and room temperature (RT), while hydrogen retention is reaching 0.37 wt % at 40 bar and RT for the washed sample. When employed as supercapacitor electrodes, these carbonaceous foams are able to deliver high capacities of ∼140 F/g at 1 A/g, thereby matching the ones obtained from a commercial carbon reference, while additionally providing a restored remnant capacity of 120 F/g at 2 A/g over 5000 cycle numbers